Tricks of the mind - Brown, Derren (Channel 4, 2007)
Derren Brown's television and stage performances have entranced and dumbfounded millions. His baffling illusions and stunning set pieces - such as "The Seance", "Russian Roulette" and "The Heist"--Have set new standards of what's possible, as well as causing more than their fair share of controversy. Now, for the first time, he reveals the secrets behind his craft, what makes him tick and just why he grew that beard. "Tricks of the Mind" takes you on a journey into the structure and pyschology of magic. Derren also takes a long hard look at the paranormal industry and why some of us feel the need to believe in it in the first place. Alternately hilarious, controversial and challengingg, "Tricks of the mind" is essential reading for Derren's legions of fans, and pretty bloody irresistible even for those who don't like him that muh ..."